Mortality rates in physician staffed ground vs. air ambulance for severe trauma patients: retrospective analysis of the Japanese nationwide trauma registry - Tomohiro Akutsu; Akira Endo; Ryo Yamamoto; Kazuma Yamakawa; Hiraaki Okuzawa; Keisuke Suzuki; Hiromasa Hoshi; Yasuhiro Otomo; Koji Morishita (Scientific Reports)
Abstract While both physician-staffed ground ambulances (GA) and air ambulances (AA) can function as viable transportation options in severe trauma cases, no study has directly compared their efficacies. We aimed to compare the effects of physician-staffed GA and AA on the outcomes of patients with trauma. This retrospective cohort study used records from the Japan Trauma Data Bank collected between April 2004 and December 2021. Data from patients aged ≥ 15 years with an Injury Severity Score > 15, who were directly transferred from the injury scenes, were analyzed. Patients were categorized into two groups based on the transportation method: physician-staffed GA and AA. The primary outcome measure (in-hospital mortality) and secondary outcomes (time to emergency department arrival, time to physician contact and prehospital treatment) were compared between the propensity score-matched groups. Of the 3,508 propensity score-matched pairs, the AA group exhibited significantly lower in-hospital mortality (810 [23.0%]) than the GA group (894 [25.4%]), odds ratio: 0.88 (95% confidence interval [CI] 0.79–0.98). Time to emergency department was significantly longer in the AA group than in the GA group. While patients in the GA group were likely to receive more treatments during transportation, patients in the AA group were likely to receive more surgical interventions after hospital arrival.